If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -92 = m + -2(10 + -4m) -92 = m + (10 * -2 + -4m * -2) -92 = m + (-20 + 8m) Reorder the terms: -92 = -20 + m + 8m Combine like terms: m + 8m = 9m -92 = -20 + 9m Solving -92 = -20 + 9m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-9m' to each side of the equation. -92 + -9m = -20 + 9m + -9m Combine like terms: 9m + -9m = 0 -92 + -9m = -20 + 0 -92 + -9m = -20 Add '92' to each side of the equation. -92 + 92 + -9m = -20 + 92 Combine like terms: -92 + 92 = 0 0 + -9m = -20 + 92 -9m = -20 + 92 Combine like terms: -20 + 92 = 72 -9m = 72 Divide each side by '-9'. m = -8 Simplifying m = -8
| 0.44-0.05x=0.25x-0.1 | | .5(x+7)-3=7 | | 4.5x+3.4=2x+8.4 | | -8(-4a-6)+3=-205 | | 4h^2+18h-26=0 | | 2(-3)+3(2)= | | 15=-15-8x | | 130-(7x+14)=7(x+8)+x | | x^2-36x=205 | | 2-8(r-5)=90 | | 3+2z-2=8z+3-5z | | 4x-3x+x+2= | | 42x=-3x^2-147 | | 6(1-7b)=-246 | | 4(3x+4)=88 | | x^2+9x+2= | | 7x+8=-83 | | 5(3n-5)+2n=-93 | | 4+3x-2=8x+3-4x | | -6-3b-4=-13 | | 3x-4x+1x-4+5x= | | 8+3t-5=8t+27-2t | | 9x+8=8-(9x-8) | | 20x^2-x=12 | | 12x+13y=156 | | 20x^2-b=12 | | n-3+2n=1 | | 6x^4-4x^3+x^2-10=0 | | 4.5+1.7n=0.08 | | 5k-6+6=0 | | 2x^3-2=0 | | 7(7x+5)=231 |